Approximation theory IV - Chui, C. K.; International Symposium on Approximation Theory (1983 : Texas); Proceedings of the International Symposium on Approximation theory held at Texas A&M University, College Station, Jan. 10-14, 1983 (New York : Academic Press, 1983)
41